Evaluasi Dampak Teknologi Dalam Pendekatan Sistem Pendidikan di SD Muhammadiyah 6 Medan - Putri Suci Ramadhani; Nur Khofifah Siregar; Melati Br. Lubis; Azwar Alamsyahdana; Ahmad Rinaldi Siregar; Maulida Yani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Technology has become an inseparable part of human life, including in the field of education. Muhammadiyah 6 Medan Elementary School (SDM 6) is one of the schools that has implemented technology in its education system approach. This research aims to evaluate the impact of technology in the education system approach in HR 6. This research is a qualitative descriptive research which aims to produce information in the form of notes and descriptive data contained in the texts studied as well as observation results. The research results show that technology has had a positive impact on the education system approach in HR 6. Technology has helped increase learning effectiveness, student motivation and the quality of education. Specifically, technology has helped teachers to deliver learning material in a more interesting and interactive manner. Technology has also helped students to learn independently and more effectively. Apart from that, technology has also helped schools to improve the quality of education by providing access to a wider range of learning resources. However, this research also found several challenges in implementing technology in the education system approach in SDM 6. These challenges include, among other things, related to the availability of infrastructure and human resources, as well as teachers' ability to use technology. In general, this research shows that technology has the potential to improve the quality of education. However, the application of technology in education needs to be done wisely and taking into account various related factors.